Comprehensive tax reform : the Colombian experience - Shome, Parthasarathi, 1950-; Dunn, David, 1958- (Occasional paper (International Monetary Fund), 1995)
This paper analyzes particular areas of tax policy that have concerned the Colombian authorities during the 1990s, while comprising a comprehensive approach to tax reform over time. It is intended to allow the reader to view in technical detail the type of analysis conducted in a representative tax reform study carried out by the IMF.